Affinity capillary electrophoresis and density functional theory study of noncovalent interactions of cyclic peptide [Gly6 ]-antamanide with small cations - Pangavhane, Sachin; Böhm, Stanislav; Makrlík, Emanuel; Ruzza, Paolo; Kašička, Václav (Electrophoresis, 2017)
ACE and density functional theory were employed to study the noncovalent interactions of cyclic decapeptide glycine-6-antamanide ([Gly6 ]AA), synthetic derivative of native antamanide (AA) peptide from the deadly poisonous fungus Amanita phalloides, with small cations (Li+ , Rb+ , Cs+ , NH4+ , and Ca2+ ) in methanol. The strength of these interactions was quantified by the apparent stability constants of the appropriate complexes determined by ACE. The stability constants were calculated using the nonlinear regression analysis of the dependence of the effective electrophoretic mobility of [Gly6 ]AA on the concentration of the above ions in the BGE (methanolic solution of 20 mM chloroacetic acid, 10 mM Tris, pHMeOH 7.8, containing 0-70 mM concentrations of the above ions added in the form of chlorides). Prior to stability constant calculation, the effective mobilities measured at actual temperature inside the capillary and at variable ionic strength of the BGEs were corrected to the values corresponding to the reference temperature of 25°C and to the constant ionic strength of 10 mM. From the above ions, Rb+ and Cs+ cations interacted weakly with [Gly6 ]AA but no interactions of [Gly6 ]AA with univalent Li+ and NH4+ ions and divalent Ca2+ ion were observed. The apparent stability constants of [Gly6 ]AA-Rb+ and [Gly6 ]AA-Cs+ complexes were found to be equal to 13 ± 4 and 22 ± 3 L/mol, respectively. The structural characteristics of these complexes, such as position of the Rb+ and Cs+ ions in the cavity of the [Gly6 ]AA molecule and the interatomic distances within these complexes, were obtained by the density functional theory calculations.
Keywords: Models, Molecular; kationty; Cesium complex; Temperature; [Gly6]-antamanide; Electrophoresis, Capillary; Spectrophotometry, Ultraviolet; Density functional theory; teplota; Cations; Solvents; molekulární modely; rozpouštědla; osmolární koncentrace; elektroforéza kapilární; cyklické peptidy; Rubidium complex; Quantum Theory; Stability constants; Peptides, Cyclic; kvantová teorie; Affinity capillary electrophoresis; spektrofotometrie ultrafialová; Osmolar Concentration